Effect of quinidine on maintaining sinus rhythm after conversion of atrial fibrillation or flutter. A multicentre study from Stockholm. Issue 5 (May 1975) - Södermark, T; Jonsson, B; Olsson, A; Orö, L; Wallin, H; Edhag, O; Sjögren, A; Danielsson, M; Rosenhamer, G
Abstract : In a controlled study comprising 176 patients, quinidine in the form of Kinidin Durules was found to reduced significantly the recurrence of the atrial fibrillation during a 1-year follow-up period after successful electric shock conversion. After one year, 51 per cent (52/101) of the patients in the quinidine group, and 28 per cent (21/75) in the control group remained in sinus rhythm (P smaller than 0.001). No less than 43 per cent of the patients converted to sinus rhythm during treatment with maintenance doses of quinidine sulphate before intended DC conversion. Gastrointestinal side-effects were not uncommon, and caused interruption of quinidine treatment in some cases.